Intelligent tools for optimizing information and search engines - Tverdokhlib, A.; Sotnik, S. (ХНУРЕ, 2024)
The study highlights transformational impact of intelligent technologies on functioning of IRS. The focus is on integration of artificial intelligence, machine learning and natural language processing, which are revolutionizing the processes of understanding user queries and providing relevant results. The paper analyzes benefits of implementing these technologies, including improved search accuracy, personalized user experience, and system adaptability. Particular attention is paid to semantic search as advanced area of IRS development. The study is not limited to theoretical aspects, but provides specific examples of intelligent tools use in leading search engines. A critical analysis of challenges and limitations of these technologies provides balanced view of their potential. Visual elements of work contribute to better understanding of complex concepts. Overall, study emphasizes key role of intelligent tools in improving IRS and their potential impact on various sectors, from scientific research to everyday access to information.
Keywords: intelligent tools; artificial intelligence; information retrieval systems; benefits